Analisis Peran Supervisor dalam Meningkatkan Kinerja Pegawai pada PT. Global Sinergi Maritim - Sukardi Sukardi (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2023)
The main objective of this research is to determine the role of supervisors on employee performance at PT. Global Maritime Synergy. The research was carried out at PT. Global Sinergi Maritime for 3 months from January - March 2024. The method used in this research is Qualitative Descriptive where researchers obtain data from various sources through Library Research and Field Research. In the field, researchers collect data using interview, observation and documentation methods. Number of Population in PT. Global Sinergi Maritim numbered 30 people. 25 respondents were taken as samples due to time constraints. The research results are as follows: Supervisors are one of the most important people in a company. because, it has quite heavy duties and responsibilities, namely managing and establishing good relationships between management levels and staff. The role of a supervisor is also very necessary in companies to improve company performance. Supervisors are part of company management who play an important role in efforts to increase productivity. Supervisor's duties and responsibilities: 1. Achieve department goals by supervising staff and managing work processes. 2 Implement and enforce systems, procedures and policies. 3. Monitor employee productivity by providing useful feedback and training. 4. Set performance targets in accordance with the organization's plans and vision. 5. Ensure compliance with laws and company policies and procedures. 6. Convey information from management to employees and vice versa. 7. Handle customer problems. 8. Assist in hiring and firing employees 9. Control budget information.